2015
DOI: 10.1074/jbc.m114.601203
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Expression of Hepatocyte Nuclear Factor 4α (Hnf4α)/MicroRNA-122 (miR-122) Axis in Hepatitis B Virus-associated Hepatocellular Carcinoma Enhances Potential Oncogenic GALNT10 Protein Activity

Abstract: Background: GALNT, the initial enzyme in mucin-type O-glycosylation, plays critical roles in cancer etiology. Results: GALNT10-induced cellular proliferation was associated with EGFR activation mediated by down-regulation of miR-122 in HBV-associated HCC. Conclusion: A regulatory pathway of Hnf4␣/miR-122/GALNT10/EGFR may represent a possible mechanism underlying HBV-associated hepatocarcinogenesis. Significance: This finding provides a novel role for O-glycosylation in HCC pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 73 publications
(68 reference statements)
5
72
0
1
Order By: Relevance
“…Although the involvement of GALNT3 in viral infections has not been demonstrated yet, recent evidence showed that the UDP-GalNAc transferase families may play important roles in viral replication (26,27). Therefore, we next investigated the regulation of GALNT3 in IAV infection.…”
Section: Downregulation Of Mirnas Targeting Galnt3 Mrna During the Eamentioning
confidence: 99%
“…Although the involvement of GALNT3 in viral infections has not been demonstrated yet, recent evidence showed that the UDP-GalNAc transferase families may play important roles in viral replication (26,27). Therefore, we next investigated the regulation of GALNT3 in IAV infection.…”
Section: Downregulation Of Mirnas Targeting Galnt3 Mrna During the Eamentioning
confidence: 99%
“…Moreover, miRNA-1231 targets pgRNA and suppresses replication (Kohno et al, 2014). Bioinformatics analyses have also identified miRNA-199a-3p, miRNA-210 and miRNA-345 binding sites on 3.5 kb RNA; miRNA-let7, −196b and −511 binding sites on 2.4 kb RNA and miRNA-433 binding on 2.1 kb RNA and miRNA-205 on 0.7kbRNA (Liu et al, 2009; Potenza et al, 2011; Wu et al, 2015; Zhang et al, 2010, 2013). However, the biological significance of these binding sites is not firmly established.…”
Section: Transcription Of Cccdna and Transport Of Rna Out Of The Nucleusmentioning
confidence: 98%
“…Meanwhile, there are several examples of miRNA-mediated GALNT expression involving in malignant biological processes of corresponding tumors (17,20,21). In this study, we screened out miR-9 as the most probable miRNA directly targeting GALNT4 in HCC cells.…”
Section: Mir-9/galnt4 Axis In Hccmentioning
confidence: 99%
“…Because previous studies have well documented that GALNT1, GALNT2, and GALNT10 can modify the O-glycosylation of epidermal growth factor receptor (EGFR) in HCC cells (13,14,17), we next aimed at distinguishing GALNT4 from these GALNTs or establishing similarities for the activity of EGFR in HCC cells. Our data showed that the membrane EGFR level was not affected by GALNT4 (Fig.…”
Section: Galnt4 Modulates the Activity Of Egfr Via O-linkedmentioning
confidence: 99%
See 1 more Smart Citation